Antimicrobial susceptibility profiles of Staphylococcus intermedius isolates from clinical cases of canine pyoderma in South Africa - Van Vuuren, Moritz (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.